CORRELATION OF EARLY MARRIAGE WITH STUNTING IN THE REGION WORK AREA OF PADANG PASIR HEALTH CENTER, PADANG CITY - Aninora, Novia Rita (Rena Cipta Mandiri, 2022)
Stunting will result in decreased productivity and quality of human resources. Adverse effects on toddlers such as brain development, intelligence, impaired physical growth, and body metabolism. The purpose of this study was to determine the correlation between early marriage and the incidence of stunting in the Padang Pasir Public Health Center, Padang City in 2021. This study is an analytic observational study with a cross-sectional design. The population in this study was toddlers aged 0-24 months whose mothers married early in the Padang Pasir District, Padang City. The study was carried out at the Padang Pasir Health Center in April-June 2021. The selection of research subjects was carried out by total sampling based on inclusion criteria, the sample size was 38 people. The conclusion was that there was no correlation between early marriage and stunting in the Padang Pasir Public Health Center, Padang City in Efforts were made to monitor routine growth at the posyandu, improve sanitation behavior and healthy clean water and the availability of nutritious and affordable food products, counseling on the topic of stunting.